The Europen Economic and Monetary Union, the Czech republic and the Theory of Optimum Currency Areas - Jurák, Jan (2006)
The paper explores the theory of optimum currency areas, outlines its implications for current international monetary order, and applies its conclusions to the European Economic and Monetary Union